Magnitude and sources of disagreement among gun policy experts - Morral, Andrew R. (RAND Corporation, 2021)
Introduction -- Sample of Policy Experts -- Survey Design and Analysis Plan -- Survey Findings -- Correlates of Experts' Divergent Views -- Developing a Gun Policy Comparison Tool Using Survey Data -- Discussion and Conclusions.